2015
DOI: 10.1016/j.neuron.2015.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin-1 Knockin Mice Reveal Loss-of-Function Mechanism for Familial Alzheimer’s Disease

Abstract: Summary Presenilins play essential roles in memory formation, synaptic function, and neuronal survival. Mutations in the Presenilin-1 (PSEN1) gene are the major cause of familial Alzheimer’s disease (FAD). How PSEN1 mutations cause FAD is unclear, and pathogenic mechanisms based on gain or loss of function have been proposed. Here, we generated Psen1 knockin (KI) mice carrying the FAD mutation L435F or C410Y. Remarkably, KI mice homozygous for either mutation recapitulate the phenotypes of Psen1−/− mice. Neith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
234
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(254 citation statements)
references
References 56 publications
13
234
6
1
Order By: Relevance
“…It is important to note that the amyloid hypothesis has been seriously challenged by studies showing that, in some cases, AD develops as a result of loss of g-secretase activity (BenGedalya et al 2015;Xia et al 2015). Moreover, in many cases, brains of individuals who suffered from AD contain no excess of Ab (Szaruga et al 2015), and transmissibility experiments strongly suggest that different, prion-like Ab strains exist (Meyer-Luehmann et al 2006).…”
Section: The Deposition Of Aggregates Is a Hallmark Of Neurodegeneratmentioning
confidence: 99%
“…It is important to note that the amyloid hypothesis has been seriously challenged by studies showing that, in some cases, AD develops as a result of loss of g-secretase activity (BenGedalya et al 2015;Xia et al 2015). Moreover, in many cases, brains of individuals who suffered from AD contain no excess of Ab (Szaruga et al 2015), and transmissibility experiments strongly suggest that different, prion-like Ab strains exist (Meyer-Luehmann et al 2006).…”
Section: The Deposition Of Aggregates Is a Hallmark Of Neurodegeneratmentioning
confidence: 99%
“…In this regard, it will be worth testing whether the Tau DN allele in heterozygosis prevents memory and synaptic deficits in KI mouse models of human dementias characterized by increased APP processing and tauopathy. 41,[49][50][51][52][53][54][55][56][57] Four things are worth noting concerning the alterations of Tau. First, we see an increase in total brain Tau levels in Tau DN/DN mice, even at young age.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have implicated that many of the EOFAD mutations actually abolish γ-secretase activity. Indeed, a recent study employed a knockin approach to investigate the effects two EOFAD PSEN1 mutations have on γ-secretase function and found that these mutations abolished γ-secretase activity (Xia et al, 2015). Correspondingly, another recent study investigated 138 distinct EOFAD PSEN1 mutations and found that 90% of these mutants decreased Aβ production (Sun et al, 2017).…”
Section: Presenilin and γ-Secretase Functionmentioning
confidence: 99%